Characterizing the biological and biochemical profile of six different scorpion venoms from the Buthidae and Scorpionidae family (2017)
The objective of this study was to characterize six different scorpion venoms using biological and biochemical methods, including a preliminary MS/MS and a post-translational modifications analysis. Despite the diversity of scorpion species of medical importance in Africa and Colombia, the venoms of these arachnids have been poorly studied in these two regions. We report the biochemical, electrophoretic, chromatographic profile, internal peptide sequences with a post-translational modification report, and a preliminary antitumor activity of five different scorpions of the Buthidae family, Androctonus amoreuxi, Babycurus jacksoni, Grosphus grandidieri, Hottentotta gentili and Tityus fuhrmanni, and one of the Scorpionidae family Pandinus imperator. No L-amino oxidase activity was detected in the evaluated venoms. Proteolytic activity using azocasein was detected only in G. grandidieri and P. imperator, indicating the possible presence of metalloproteinases in these two venoms. Proteolytic activity using NOBA was detected in all venoms indicating the possible presence of serine-proteinases. Phospholipase A2 activity was detected in the venoms of P. imperator, G. grandidieri, H. gentili and A. amoreuxi, with P. imperator venom being the most active. All venoms analyzed contained defensin-like proteins, alpha toxins, metalloproteinases, neuropeptides, DBP affecting ion channels, DBP with antimicrobial activity, among others. Venoms from P. imperator, G. grandidieri and T. fuhrmanni showed a dose-dependent cytotoxic activity over MCF-7 cells. Only two isolated RP-HPLC fractions from P. imperator and T. fuhrmanni showed cytotoxic activity over MCF-7. No cytotoxic activity was found in the venoms from A. amoreuxi, B. jacksoni, and H. gentili. © 2017 Elsevier Ltd